How 'smart' are Smart Specialisation strategies? - Marco Di Cataldo; Vassilis Monastiriotis; Andrés Rodríguez-Pose (London School of Economics and Political Science (LSE), European Institute, 2020)
The introduction of Smart Specialisation (S3) as a fundamental pillar of the 2014 reform of the European Union (EU) Cohesion Policy has represented a significant strategic shift in European development intervention. S3 strategies are aimed at mobilising the economic potential of each country and region of the EU, by allowing a more place-based and bottom-up approach to development. However, despite the salience that S3 has acquired in a short period of time, there has been no Europeanwide evaluation of the extent to which S3 strategies truly reflect the economic characteristics and potential of the territories where they are being implemented. This paper examines the characteristics of S3 strategies across Europe – by focusing on their development axes, economic/scientific domains, and policy priorities – to assess whether this is the case. The results show that S3 strategies display a proliferation of objectives, a problem which particularly affects those areas with weaker government quality. Moreover, strategies are generally loosely connected with the intrinsic conditions of each region and mostly mimic what neighbouring areas are doing. The lack of more concise and focused S3 strategies is likely to undermine the effectiveness of what is, otherwise, a very interesting and worthwhile policy experiment.
Keywords: 330; Smart Specialisation; EU Policy; regions; Europe